2017
DOI: 10.1111/epi.13860
|View full text |Cite
|
Sign up to set email alerts
|

Seizure outcome after hippocampal deep brain stimulation in patients with refractory temporal lobe epilepsy: A prospective, controlled, randomized, double‐blind study

Abstract: Hip-DBS was effective in significantly reducing seizure frequency in patients with refractory TLE in the active group, as compared to the control group. Fifty-percent of the patients in the active group became seizure-free. The present study is the larger prospective, controlled, double-blind study to evaluate the effects of Hip-DBS published to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 18 publications
5
82
2
2
Order By: Relevance
“…Thus, according to a randomized study, assessing the effectiveness of hippocampal stimulation in patients with temporal lobe DRE, a positive effect in the form of complete disappearance of seizures was found in 50% of patients. (27) Other studies have shown that after 11 years of deep brain stimulation, the attacks were not registered for at least 12 months in only 13.8% of the patients. (28) The principle of this method lies in electrode implantation into certain brain structures (target-structures); these electrodes are supplied with low voltage and high frequency electric current.…”
Section: Deep Brain Stimulationmentioning
confidence: 94%
“…Thus, according to a randomized study, assessing the effectiveness of hippocampal stimulation in patients with temporal lobe DRE, a positive effect in the form of complete disappearance of seizures was found in 50% of patients. (27) Other studies have shown that after 11 years of deep brain stimulation, the attacks were not registered for at least 12 months in only 13.8% of the patients. (28) The principle of this method lies in electrode implantation into certain brain structures (target-structures); these electrodes are supplied with low voltage and high frequency electric current.…”
Section: Deep Brain Stimulationmentioning
confidence: 94%
“…The majority of patients (n = 27) had generalized or secondarily generalized seizures ( Table 2). Four patients had previous episodes of status epilepticus, 7,24,45 including 1 patient who was in a continu-ous 4-week episode of intractable status epilepticus, which only improved after DBS treatment. 24 Five patients had previous surgery in an attempt to treat their epilepsy.…”
Section: Seizure Characteristicsmentioning
confidence: 99%
“…DBS has also been considered in children who have already undergone resective surgery without significant post-operative seizure reduction [14,24,25]. DBS has been used in four children who had a history of status epilepticus with an improvement in seizure frequency in three of these children [15,26].…”
Section: Predictors Of Responsementioning
confidence: 99%